Opini Ephorus & Kepala Departemen Marturia tentang Peran dan Fungsi Paduan Suara dalam Liturgi di Gereja Punguan Kristen Batak (GPKB) (Jurnal Pendidikan Agama dan Teologi, 2025)
This study aims to determine the opinions of two central figures in the GPKB structure, namely Ephorus and Head of Department Marturia, regarding the role and function of the choir in the liturgy. The background of this study is based on the observation that in many worship practices within the GPKB environment, the choir is often considered only an aesthetic complement, without considering the theological and liturgical meaning that should accompany it. Using a qualitative descriptive approach, data were obtained through in-depth interviews with key informants, direct observation of liturgical implementation, and a review of church documents such as the Order of Worship. Analysis was carried out carefully to explore the perceptions, expectations, and direction of church policy regarding choir ministry. The results show that both Ephorus and Head of Department Marturia view the choir as a liturgical servant on a par with servants of the word. They emphasize that the choir must be a means of proclaiming the word through theologically and contextually weighty music. However, they also acknowledge that implementation at the congregation level is not yet consistent, and guidance for the choir is still minimal in the liturgical and spiritual aspects.